High Value-Added Application of Two Renewable Sources as Healthy Food: The Nutritional Properties, Chemical Compositions, Antioxidant, and Antiinflammatory Activities of the Stalks of Rheum officinale Baill. and Rheum tanguticum Maxim. ex Regel - Dai, Li-Xia; Miao, Xiaolou; Yang, Xiao-Rong; Zuo, Li-Ping; Lan, Zhi-Hui; Li, Bing; Shang, Xiao-Fei; Yan, Feng-Yuan; Guo, Xiao; Wang, Yu; Zhang, Ji-Yu (Frontiers in Nutrition, 2022)
Rhubarb plants (Rheum officinale and R. tanguticum) have edible stalks. In this study, we aimed to compare the nutritional properties, chemical compositions and bioactivities of R. officinale (SRO) and R. tanguticum (SRT) stalks and to analyze the composition-function relationship. Results showed that the two stalks were good sources of fiber, as well as minerals. They contained abundant essential amino acids and essential fatty acids to regulate the immunity and prevent some chronic diseases, the contents of polyunsaturated fatty acids were 2244.32 mg/100 g and 2844.69 mg/100 g, respectively. The antioxidant activity also were proved. Metabolomics showed that SRO and SRT contained the abundant of phenolic acids. Due to the higher concentrations of flavones, SRT has the better anti-inflammatory activities than SRO by inhibiting NF-κB signaling pathway. Rhubarb stalks exhibited good safety in acute toxicity and cytotoxicity tests. This study indicated that the two stalks have nutritional value, safety, and bioactivities, and could be used as sources of nutritional ingredients for regulating the immunity of body in food industry.